Between Narratives and Climate Justice: Globo and UOL’s Coverage of Activism at the COPs - Tainá Yumi Patriani; Ergon Cugler de Moraes Silva (Ambiente & Sociedade, 2025)
Abstract Although climate change is increasingly covered in the media, the narratives surrounding socio-environmental issues have never been neutral or unified. This study examines how the largest Brazilian media conglomerates, Globo and UOL, covered the popular protests during the 26th and 27th editions of the United Nations Conference on Climate Change (Conference of the Parties - COP). We intended to identify the main themes of the news articles published on these portals regarding the protests and discuss them through the lens of climate justice. Content analysis assisted by unsupervised Artificial Intelligence (AI) was used to cluster 45 news articles. The results reveal three distinct thematic clusters: “Activist Greta Thunberg”, “Popular Demands”, and “Commitments of the Parties”. Except for one news article, the narratives found do not promote climate justice. Additionally, more than half of the news articles were from international agencies.